Improved Method of Contrast-enhanced Ultrasound examination of the Kidneys in Patients with Type 2 Diabetes Mellitus - A. V. Borsukov; O. A. Gorbatenko (Acta Biomedica Scientifica, 2021)
Aim of the research. Тo evaluate the diagnostic efficacy of the contrast-enhanced ultrasound examination of kidneys in patients with type 2 diabetes mellitus with a dose of 0.5 ml of contrast agent administered.Materials and methods. We examined 12 patients with a verified diagnosis of type 2 diabetes. The age of the examined patients was 31–59 years, the mean age was 49 ± 1.3 years. All patients underwent complex diagnostics, including ultrasound examination of the kidneys in B-mode with further renal vessels color Doppler imaging to assess vessels hemodynamics. A contrast-enhanced ultrasound examination of the kidneys was carried out using Sonovue contrast agent at the doses of 2.5 ml (according to the European Good Clinical Practice Recommendations for Contrast-Enhanced Ultrasound) and 0.5 ml (an improved technique of contrast agent intravenous bolus administration).Results. The improved technique (0.5 ml of contrast agent intravenous bolus administration) in comparison with the European Recommendations technique (2.5 ml of contrast agent intravenous bolus administration) used in patients with type 2 diabetes showed no or minor differences in the qualitative and quantitative indicators of contrast-enhanced ultrasound examination which did not affect the interpretation of the results.Conclusion. The improved contrast-enhanced ultrasound examination technique using 0.5 ml of a contrast agent showed its possibilities in diagnosing diabetic nephropathy in patients with type 2 diabetes, and also revealed the potential of an economically beneficial distribution of a contrast agent without losing the quality and information content of the study.